Recombinant protein and DNA vaccines derived from hsp60 Trichophyton mentagrophytes control the clinical course of trichophytosis in bovine species and guinea-pigs - Milan, Raska; Alois, Rybnikar; Josef, Chumela; Jana, Belakova; Evzen, Weigl (Mycoses, 2004)
Heat shock proteins (hsp) were identified in many infectious agents as immunodominant antigens with a protective effect. Immunization of laboratory animals by selected representants of hsp60, hsp70 and hsp90 isolated from several pathogens induced protective host immunity and significantly reduced clinical manifestation of infection. The present study involves preparation of a recombinant protein vaccine and a DNA vaccine. Both vaccines were derived from the hsp60 of the dermatophyte, Trichophyton mentagrophytes. Challenge trials with evaluation of the protective effect of vaccination were performed on calves and guinea-pigs. Both vaccination procedures reduced, in statistically significant fashion, the clinical course of skin mycosis in calves experimentally inoculated with the dermatophyte, T. mentagrophytes. In experiments with guinea-pigs, increased protection was only seen with DNA vaccination. After DNA vaccine application, no paravaccination side-effects (granulomas at the injection site, changed total state of the animal) were observed. Only vaccination with the recombinant protein in calf's experiment induced specific serum antibodies. This observation indicates that antibodies are not associated with protection. In summary, DNA vaccine hsp60 is the most promising for prevention of bovine trichophytosis.
Keywords: nemoci skotu; chaperon hsp60; Chaperonin 60; fungální vakcíny; Recombinant Proteins; zvířata; Vaccines, DNA; Guinea Pigs; rekombinantní proteiny; Cattle; Cattle Diseases; skot; morčata; tinea; Tinea; Animals; DNA vakcíny; Fungal Vaccines; Trichophyton